Density, abundance and distribution of the guiana dolphin, (Sotalia guianensis van Benéden, 1864) in Sepetiba Bay, Southeast Brazil - Flach , Leonardo; Flach , Patricia Amaral; Chiarello , Adriano G. (J. Cetacean Res. Manage., 2023)
Line transect surveys were conducted from August 2002 to July 2003 to examine the abundance and distribution of the guiana dolphin (Sotalia guianensis) in Sepetiba Bay-Southeast Brazil. A boat-based platform and 50 pre-determined line transects were used to assess the population on two main stratum-specific environments of the bay (entrance and interior). A total of 3,140km of transects were surveyed at 12-15km hr–1 and good sea conditions (Beaufort 0-2), resulting in 157 sightings of dolphin groups and 129 sightings after truncation of all sightings beyond 400m. From the 129 sightings the DISTANCE program generated a population density of 2.79 dolphins km–2 and calculated a population of 1,269 individuals (CI=739-2,196) for the bay. Sighting frequency (n=126 or 80.3%) was higher at the entrance of the bay compared with the interior (n=31 or 19.7%), although, the density and abundance were similar for the entrance (2.91 dolphins km–2 and 596 dolphins) and interior (2.69 dolphins km–2 and 672 dolphins). Results reveal an important population of guiana dolphin at Sepetiba Bay, the largest thus far studied off the South American coast, stressing the importance of the area for the conservation of this species. The study also indicated that line-transect sampling carried out from small boats in large bays can produce statistically robust estimates and therefore could be recommended for population monitoring in other areas of the Brazilian coast with similar characteristics.